2017
DOI: 10.1016/j.jde.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Global well-posedness of the derivative nonlinear Schrödinger equation with periodic boundary condition inH12

Abstract: Abstract. We establish the global well-posedness of the derivative nonlinear Schrödinger equation with periodic boundary condition in the Sobolev space H 1 2 , provided that the mass of initial data is less than 4π. This result matches the one by Miao, Wu, and Xu and its recent mass threshold improvement by Guo and Wu in the non-periodic setting. Below H 1 2 , we show that the uniform continuity of the solution map on bounded subsets of H s does not hold, for any gauge equivalent equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Wu [75,76] showed that it is globally well-posed in H 1 (R) under the condition u 0 L 2 < 2 √ π. Guo and Wu [21] later proved that it is globally well-posed in H 1 2 (R) under the same condition of initial data, see also [9,10,61] for the previous results on the low regularity. The same results also hold in the periodic case, see Mosincat and Oh [59] in H 1 (T), and Mosincat [58] in H 1 2 (T). More recently, Jenkins, Liu, Perry and Sulem [38] proved that the Cauchy problem (1.2) is globally well-posed in the weighted Sobolev space H 2,2 (R).…”
Section: Introductionsupporting
confidence: 62%
“…Wu [75,76] showed that it is globally well-posed in H 1 (R) under the condition u 0 L 2 < 2 √ π. Guo and Wu [21] later proved that it is globally well-posed in H 1 2 (R) under the same condition of initial data, see also [9,10,61] for the previous results on the low regularity. The same results also hold in the periodic case, see Mosincat and Oh [59] in H 1 (T), and Mosincat [58] in H 1 2 (T). More recently, Jenkins, Liu, Perry and Sulem [38] proved that the Cauchy problem (1.2) is globally well-posed in the weighted Sobolev space H 2,2 (R).…”
Section: Introductionsupporting
confidence: 62%
“…The highest value of the mass for which global existence in H 1 (T) holds is δ = 2 π/|β|. This was shown for the non-periodic framework in [Wu13] and the argument was adapted to periodic DNLS in [MO15] (similarly, for the best result in H 1 2 (T) see [Mos17]). Existence of global solution of DNLS on R without any condition on the mass has been proven by inverse scattering method in [LPS16].…”
Section: Introductionmentioning
confidence: 79%
“…The result in [49] was extended to the periodic setting in [35]. Finally, the argument in [5] was further advanced in [12,34] to treat the endpoint case s = 1 2 and M (q) < 4π; see also [47] for earlier work in the periodic setting.…”
Section: Introductionmentioning
confidence: 99%